Intervención de enfermería en la prevención de estrés preoperatorio en pacientes adultos mayores: revisión sistemática - Martínez Erazo, Paola Milena (2025)
Preoperative stress prevention in older adult patients is a crucial aspect of medical care that can significantly influence surgical outcomes and postoperative recovery. The objective is to determine nursing interventions in the prevention of preoperative stress in older adult patients through a systematic documentary review of the last 5 years. It was used to explore in depth through the documentary review to interventions for preoperative stress, where key factors that influence the effectiveness of these interventions will be identified. Following the previously established inclusion and exclusion criteria, 80 articles related to nursing staff intervention in the prevention of preoperative stress in older adult patients were identified. The results of this systematic review highlight the importance of tailoring nursing interventions to the specific needs of the geriatric patient, considering factors such as frailty, polypharmacy and comorbidities associated with aging, whereby the implementation of preoperative nursing visits and detailed individual risk assessment allow early identification of stressors, facilitating an adjusted care plan that not only improves the surgical experience, but also optimizes postoperative outcomes. Nursing interventions focused on effective communication, personalized education and non-pharmacological techniques, such as motivational interviewing and guided relaxation, proved to be effective strategies to reduce preoperative stress and anxiety in older adult patients.